2009
DOI: 10.1080/17439880903141521
|View full text |Cite
|
Sign up to set email alerts
|

Trainee teachers’ use of blogs as private reflections for professional development

Abstract: Developments in Higher Education (HE) over the last decade have seen an increasing focus on developing skills through the use of technology as part of blended learning opportunities. At Sheffield Hallam University (SHU) and Nottingham Trent University (NTU) in the United Kingdom research has taken place over the last year in the use of personal diaries with trainee teachers using a private web log (blog). The purpose of the research was to determine if blogs could provide a setting for their continuing profess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 22 publications
3
28
0
3
Order By: Relevance
“…This can be interpreted as one reason why the texts were mainly descriptive and retrospective i.e. they handled everyday experiences in a reporting way without taking alternative or critical stands, and complies with findings in Hramiak et al (2009) and Kerawalla et al (2008). In their studies on student teachers writing reflective blogs, the first phase of learning to reflect involves being used to the writing process itself.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This can be interpreted as one reason why the texts were mainly descriptive and retrospective i.e. they handled everyday experiences in a reporting way without taking alternative or critical stands, and complies with findings in Hramiak et al (2009) and Kerawalla et al (2008). In their studies on student teachers writing reflective blogs, the first phase of learning to reflect involves being used to the writing process itself.…”
Section: Discussionmentioning
confidence: 93%
“…A major concern related to projects working with reflection as a methodological approach, is that they tend to finish after the first phase (Hramiak et al, 2009), a phase we identified as a preparatory phase. This study contributes to…”
Section: Final Conclusionmentioning
confidence: 99%
“…Because CMC communication does not provide visual or intonation cues, participation does not necessarily establish trust or a sense of community among members (Paulus & Scherff, 2008) and thus the underlying technologies must be able to support artefacts creation, collaboration, awareness, and a friendly user interface (Kostas & Sofos, 2012 these research studies were subject to various conditional factors, such as the need of a sound instructional design in order to achieve reflective practice (Whipp, 2003), the type of messages, i.e. positive vs. negative ones (Ebenezer, 2003), the need for a clear goal for the community, a better framing of the communication with emphasis on the CMC environment (Hough, Smithey, & Everston,, 2004), teacher's presence (Yang, 2009), individual's skills (Hramiak, Boulton & Irwin, 2009) and lack of participants' time (Andersen & Matkins, 2011). Summary of the literature review's outcomes leads to some basic requirements needed for the sustainable pedagogical and technological settings of a CMC platform, as a supportive environment for student teacher's apprenticeship:  Members of a supportive community must have access to a set of various tools (asynchronous and synchronous) within the same infrastructure.…”
Section: Review Of Technologies In Support Of Student Teachers' Practmentioning
confidence: 99%
“…Otra preocupación general es la referida a la confidencialidad de lo escrito en el diario (29,43,56,57) y que podría condicionar su contenido, aspecto que se agrava cuando lo escrito es público, como es el caso de blogs compartidos para este fin (43,57).…”
Section: Dificultades En La Escritura Del Diariounclassified